METODE KISAH DALAM PERSPEKTIF AL-QUR’AN - Sehat Sultoni Dalimunthe (UIN Sumatera Utara Medan, 2016)
Stories Methods in the Perspective of the Qur'an. In the modern educational system method is part of the curriculum. One method of education is stories methods. This method, if done professionally can be interested for listeners. This method is suitable for telling example of the figures or events that difficult to find the data and the facts or because of other factors. In the Qur'an contains stories of the prophets, the story of the past, the events that occurred and will occur. There is also a story that is not an event, but just as the teaching and guidance.Keywords: Islamic education, the method acts, al-Qur'an.